HTLV-1 Is Also a Sexually Transmitted Infection - Martel, Mariana; Gotuzzo, Eduardo (Frontiers in Public Health, 2022)
HTLV-1 is a retrovirus which causes diverse diseases to 10% of its infected population, significantly worsening their quality of life and mortality rate. Possessing global distribution and being endemic in many countries (including Peru), it is still highly neglected. It spreads through vertical, sexual and parenteral transmission. As there doesn’t exist an effective treatment against this virus, prevention is required to contain it. The WHO published a technical report on the matter this year, with the collaboration of international HTLV-1 experts. Nonetheless, the impact of sexual transmission (cause of the majority of adult cases and infection in non-endemic areas) nor its prevention were considered. Evidence is hereby presented, which shows the magnitude of sexual transmission, its risk factors and preventive measures; hoping it will encourage health workers to help eradicate this infection.